Medical Images are Safe - an Enhanced Chaotic Scrambling Approach. - Mohamed Parvees, M.; Abdul Samath, J.; Parameswaran Bose, B. (Journal of Medical Systems, 2017)
The patient data confidentiality is one of the vital security aspects in e-Health and m-Health services. In particular, providing confidentiality to the patient's medical image is essential and the protection approaches have to be explored in-depth due to the rapid progress in the technologies of teleradiology and PACS. In this study, the pseudo random number generators (PRNGs), namely, the linear congruential generator (LCG) and XOR shift generator (XSG) are improved and combined with improved logistic 2D coupled chaotic map to provide enhanced chaos based encryption. The proposed scheme encrypts the Digital Imaging and Communication in Medicine (DICOM) images to protect the patient confidentiality during the storage and transfer in radiological information system (RIS). The cipher image was measured with various security analyses and tested with different test suites to prove its randomness.